1985
DOI: 10.1007/bf01806017
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular biologic alterations in human breast cancer: A review

Abstract: Chromosomal and molecular biologic studies of human breast cancer are beginning to provide insight into the basic biology of this important disease. The current state of knowledge of both cytogenetic evaluation and assessment of expression and amplification of cellular oncogenes in breast cancer will be outlined in this brief review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 26 publications
2
40
1
Order By: Relevance
“…In his review of human breast cytogenetics, based principally on unbanded cases, Sandberg (1980) stated that diploid metaphases are occasionally observed. Trent (1985) also cited the work by Wolman (1983), who found karyotypically normal diploid cells in primary mammary adenocarcinomas but not in metastatic effusions. These authors all concluded that acquisition of an abnormal karyotype is indicative of malignant progression rather than initial events in tumorigenesis.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In his review of human breast cytogenetics, based principally on unbanded cases, Sandberg (1980) stated that diploid metaphases are occasionally observed. Trent (1985) also cited the work by Wolman (1983), who found karyotypically normal diploid cells in primary mammary adenocarcinomas but not in metastatic effusions. These authors all concluded that acquisition of an abnormal karyotype is indicative of malignant progression rather than initial events in tumorigenesis.…”
Section: Resultsmentioning
confidence: 98%
“…These authors all concluded that acquisition of an abnormal karyotype is indicative of malignant progression rather than initial events in tumorigenesis. As mentioned by Trent (1985) and Smith et al (1985), it could be questioned whether diploid cells are really representative of the tumoral population. In culture since October 1985, cell line CAL51 has conserved a diploid karyotype with normal chromosomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In primary cell cultures of breast tumors, only a minority of cells is mitotic and few of these mitoses could be analyzed (22,23). This problem was further confounded by the observation that the few highly selected cells that could be analyzed karyologically differ greatly among even those from the same tumor (22,23).…”
Section: Discussionmentioning
confidence: 99%